A Prospective Study of Etiology and Clinical Presentation of Gastric Adenocarcinoma - Avinash Rinait1 , Yashwant R. Lamture2 , Pulavarty Prateek3 , Dilip Gode4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Dietary factors, Smoking, Alcohol, H. Pylori all have been linked to gastric carcinoma andmost of them are modifiable which can reduce the risk of cancer hence this study was undertaken to studythe etiology of gastric adenocarcinoma and its clinical presentation.Methodology: This was a prospective study in which 50 patients of gastric adenocarcinoma admitted in thesurgery department at a tertiary hospital were studied.Results: Out of 50 patients studied, 36 were males and 14 were females. The risk factors like H. pyloribiopsy, heredity, salt and preserved food were found less in the cancer patients while alcohol was found to bemore in them. Smoking was present equally in both the groups. Vomiting (100%) and loss of weight (100%)were the most common presenting feature. 46% had a Karnofsky score more than 80.Conclusion: Alcohol is a risk factor for gastric adenocarcinoma and loss of weight and vomiting are commonclinical presentation.